PENERAPAN LITERASI INFORMASI DALAM EKSPRESI DIRI TERHADAP PUSTAKAWAN DI BALAI LAYANAN PERPUSTAKAAN DPAD DIY - Tiara Ika Lestari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This study aims to apply information literacy as a form of self-expression and demonstration of literacy skills. Information literacy includes the ability to access, evaluate and use information that is currently very important to master. Information literacy has a great influence on the acquisition of other skills needed in everyday life. Information literacy consists of the ability to access, analyze, evaluate, and create messages in various forms, create an understanding in society, and build important skills from information resulting from investigation and self-expression and demonstration. This research uses descriptive method and focuses on case studies. Through a descriptive approach, the researcher will illustrate specific details regarding the circumstances, location, and social relations that take place in the research subject. And using triangulation techniques and for the process of collecting research data. Researchers conducted observations, interviews, and documentation for the same data source simultaneously.